Notions directrices et architectonique de la métaphysique. La critique kantienne de Wolff en 1763 - Stefanie Buchenau (Astérion)
This paper presents Christian Wolff’s argument on the evidence of metaphysical principles as expounded in his article Directive notions and the true use of the first science (1729). This article was a central and yet forgotten reference for those who responded to the 1762/1763 academy questions such as Kant. Wolff here asserts that metaphysics has a kind of certainty that is equal or even superior to mathematics and that it communicates such certainty to the remaining sciences. It is this Wolffian thesis that Kant attacked in 1763. A closer reading allows to acknowledge more philosophical premises of Wolff’s argument. Wolff’s thesis on the mathematical certainty of metaphysics inverts the former order of priorities between metaphysics (ontology) and mathematics. According to Wolff (who here seemed to be influenced by Euclides’ geometry), metaphysical notions are at the foundation of mathematical and logical rules. Notions such as “identity”, “thing”, “possibility” etc. have a “directive” or methodical status : they direct the mind searching the truth. Together, these notions constitute a modern and “architectonic” ontology. This framework shows the methodological continuity between Wolff and Kant. Even though Kant contested the form of Wolff’s system, his response still formed part of the general program sketched by Wolff. Kant still attempted to found some kind of architectonic metaphysics containing a table of directive concepts. From this viewpoint, Kant owes more to Wolff than what has been commonly assumed, and the deep and complex debate between the two thinkers calls for more attention.